The Chinese discourse for Africa: The importance of FOCAC and the Forum Macau on China’s regional diplomacy - Marrafa, Patrícia Alexandra Correia da Silva (2025)
From the start of the 21st century, China has invested in the development of cooperation mechanisms with specific groups of countries that complement the already existing bilateral mechanisms through the form of regional forums. These new cooperation forums have been accompanied by an expansion and growing investment in soft power initiatives, going beyond the cultural aspect, and further incorporating foreign policy mechanisms and economic statecraft in China’s diplomatic approach to their partner countries. It becomes then imperative to consider discourses produced by Chinese politicians, representatives, and researchers as important material of study to understand China’s intentions and messages for the international community, and how the country’s increased involvement with important organizations expands her international 1political stand, helps in the projection of soft power, and additionally promote China’s development model. As such, we aim to analyze how China’s discourse for Africa evolved under FOCAC and Forum Macau, by dividing our work into two phases: (I) Delivery of a diachronic perspective of the evolution of China-Africa ties, together with the importance given by the country to the global south and why it is important to look at this relationship through a complementary lens of Chinese international relations theories, and (II) Analyze how China’s discourse for Africa has been molded under her multilateral forums and how can it help in creating relations between Africa and China as well as creating an economic route through the Belt and Road Initiative (BRI).